Pelatihan Pembuatan Filtrasi Sederhana Karang Taruna Miftahul Jannah Dalam Membangun Kesehatan Lingkungan Sungai - Alawiyah, Tuti; Yuwindry, Iwan; Nurhayati, Nurhayati (Indonesia Berdaya, 2023)
Sasirangan liquid waste as a form of the textile industry has a high polluting power so it does not meet the requirements to be discharged into the environment before being processed. Sasirangan wastewater pollution parameters exceed the textile industry wastewater quality standards. Until now, in the Sungai Jingah Village there is no institutional team structure to overcome these weaknesses in waste management. Therefore, we carry out a program that can solve these problems, namely by optimizing the function of the Miftahul Jannah Youth Organization, which is domiciled in the local environment, namely the Partner Assistance Program with the theme "Training in Making Simple Filtration of Miftahul Jannah Youth Organization in Building River Environmental Health". This partner mentoring program aims to improve partner skills so that they can independently manage the waste management process for IKM sasirangan fabrics in the Sungai Jingah sub-district. The method of activity in overcoming this problem is by providing counseling regarding the chemical content and effects of sasirangan cloth waste, training on making activated carbon from banana peels, and training on making simple activated carbon filtration. Training and mentoring activities for making this Simple Filtration Economically can help increase partners' knowledge for handling sasirangan waste at Sasirangan cloth SMI Sungai Jingah Village.